Fundamental Motor Skills Mediate the Relationship Between Physical Fitness and Soccer-Specific Motor Skills in Young Soccer Players - Kokstejn, Jakub; Musalek, Martin; Wolanski, Pawel; Murawska-Cialowicz, Eugenia; Stastny, Petr (Frontiers in Physiology, 2019)
Fundamental motor skills (FMS) are the basic building blocks of more complex, sport-specific skills and should be mastered at the end of early childhood; however, the relationship between the two has not yet been verified in prepubertal soccer players. Therefore, the aim of this study was to determine the role of FMS in a process of acquiring soccer-specific motor skills (measured using the speed dribbling) with regard to physical fitness and biological maturation. Forty soccer players (11.5 ± 0.3 years of age) at the highest performance level participated in the study. The role of FMS in a complex theoretical model with the relationships among physical fitness, biological maturation and speed dribbling was analyzed by multiple regression path analyses (MRPA). Moderate-to-strong correlations were found between FMS, physical fitness, and speed dribbling (r = 0.56 – 0.66). Moreover, biological maturation did not appear to be a significant predictor of physical fitness or speed dribbling. The MRPA model of physical fitness on speed dribbling with FMS as a mediator showed a significant indirect effect (standard estimation = -0.31, p = 0.001; R2 = 0.25). However, the direct correlation between physical fitness and speed dribbling was nonsignificant. Our results showed that FMS significantly strengthened the influence of physical fitness on the performance of speed dribbling, a soccer-specific motor skill, and thus played an important role in the process of the acquisition of sport-specific motor skills in prepubertal soccer players. Therefore, when considering the long-term training process, especially during childhood and before puberty, a wide range of FMS activities should be applied for better and possibly faster acquisition of soccer-specific motor skills.